Coordination System Between Financial Services Authorities And Deposit Guarantee Insittutions In Handling Failed Banks Based On Law Number 21 Year 2011 Concerning Financial Services Authorities - King Richter Sinaga (Journal of Law Science, 2022)
The occurrence of the monetary crisis in 1997-1998 has become a very valuable lesson for the Indonesian people, especially for the government. The crisis resulted in reduced public confidence in existing banks. In order to restore public confidence in banking, the government established a government guarantee called a blanket guarantee. As the times progressed, the government guarantee was no longer effective, and then the Deposit Insurance Corporation was formed. The LPS' task is to carry out deposit insurance and actively participate in maintaining banking stability. In addition, IDIC is also tasked with handling failed banks, both with systemic and non-systemic impacts. The Financial Services Authority was established by law, namely Law Number 21 of 2011 concerning the Financial Services Authority. OJK is an institution that is independent and free from interference from other parties, which has the functions, duties and authority to regulate supervision, examination and investigation. OJK's independence will be fully effective if there is Good Corporate Governance in the financial and banking world. Because the implementation of the Good Corporate Governance system has consistently been proven to improve quality and can also become an obstacle to performance engineering activities which result in financial statements not reflecting the company's fundamental values. LPS and OJK cooperate in handling failed banks. In terms of handling failed banks, Bank Indonesia also plays a role in assisting LPS and OJK. IDIC will rescue systemic and non-systemic failed banks. For failed banks that are not systemic, the rescue does not include the old shareholders. This means that all costs incurred for the rescue will be provided by the IDIC.